The Burden of Malnutrition among Children: A Case of Kisumu County - Sawe, C. J.; Kogi-Makau, W.; Ettyang, G. A. K.; Kimamo, C. O. (Africa Environmental Review Journal, 2021)
The combination of childhood underweight and overweight are challenges facing Kenya and Sub-Sahara Africa. The prevalence of these forms of malnutrition has been escalating with the main causes being poor policies and household food insecurity. This study aimed at assessing the prevalence and determinants of childhood underweight and overweight in Kisumu County, Kenya. A quantitative cross-sectional study design was employed with 415 children aged below 24 months recruited in the study. Children were grouped into age strata then randomly selected into the study. Child’s weight, date of birth was collected and Weight for Age Z-scores calculated based on WHO Z-scores. Chi-square tests analyzed the association between childhood malnutrition and the independent variables while multinomial logistic regression determined the effect of outcome variable on the independent variables. The level of significance was set at P≤0.05. A total of 10% and 13% of children were underweight and overweight respectively. Only 47% of children were exclusively breastfed with 17% having stopped taking breast milk when they were aged 6 months and below. Chances of being underweight were 4 times high for children aged between 6 to 12 months [RRR: 4.959: 95% CI: 1.278-19.248; p=0.021], 5 times high for those whose mothers were either single or divorced or married [RRR: 4.581: 95% CI: 1.778 -11.801; p=0.002] while risks of being overweight were 50% high among still breastfeeding [RRR: 4.761: 95% CI: 1.251–18.114; p=0.022] and 30% high for those whose parents paid house rent of more than Ksh 3,000 per month [RRR: 3.344: 95% CI: 1.199–9.325; p=0.021]. Strategies to promote education on breastfeeding, house ownership, marriage, child care and nutrition interventions targeting children below two years were recommended.